DETERMINANTS OF TRADERS' INCOME IN TRADITIONAL MARKET GAMPING SLEMAN YOGYAKARTA - Muhammad Zulfikar Yusuf (Econosains Jurnal Online Ekonomi dan Pendidikan, 2023)
This study aims to analyze the factors that influence the income of traders in the Gamping traditional market, Sleman Regency, Special Region of Yogyakarta. The variables used are business capital, education, business location, trader services, and length of business. The research data type is primarily obtained through a questionnaire given to 102 traders in the Gamping Traditional Market. This study uses a quantitative approach with multiple linear regression methods. The test results show that business capital, trader services, business location, and length of business have a partial effect on market trader income with a probability value of <0.05. In comparison, the education variable does not affect the income of market traders, with a probability value of > 0.05.